Vitrification of a small number of spermatozoa in normozoospermic and severely oligozoospermic samples. (21st November 2014) - Kuznyetsov, Valeriy; Moskovtsev, Sergey I.; Crowe, Michael; Lulat, Ayub G.-M.; Librach, Clifford L.
Abstract: Despite broad utilization of sperm cryopreservation, little progress has been made to modify freezing protocols or to improve rates of sperm survival. Vitrification is an alternative method for freezing human spermatozoa without toxic permeable cryoprotectants (CPAs). The purpose of our study was to optimize the vitrification and post thaw recovery of a small number of spermatozoa using only nonpermeating CPAs in a closed straw system in normozoospermic and severely oligozoospermic samples. Individual motile spermatozoa ( n = 295) were selected from semen samples of 15 normozoospermic and 10 severe oligozoospermia patients. Overall sperm recovery after vitrification was 80% ( n = 236) with 80% ( n = 189) viability and 41.5% ( n = 98) retained post-warming motility. Two different loading techniques were compared to transfer selected spermatozoa into straws in preparation for vitrification: by spontaneous capillary action (CA) and with the aid of a polar body biopsy (PBB) pipette. There was evidence that the PBB loading technique increases the odds of spermatozoa recovery in both subsets ( p = 0.01 and p = 0.04) in the normal and abnormal subsamples, respectively.